Gerenciamento Hierá rquico de Ambientes Inteligentes Utilizando SNMP - Conceição, Denilson Rosa da; Silva, Jonas Ayres da; Azzolini, Mathias Gheno; Lunardi, Roben Castagna; Esteves, Rafael Pereira (Anais do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC), 2017)
Smart environments are designed to improve our daily lives by providing means to monitor a physical environment and react to the context in automatic and proactive ways. These environments are typically composed by a variety of sensors, actuators, and controllers interconnected by a network infrastructure. In order to allow interoperability with current Internet, such devices need to support a TCP/IP stack relying on IPv6 for addressing. Proper management of smart devices is required to allow a human operator to gather updated statistics and perform remote management over smart devices. In this paper, we investigate the use of SNMP, the de facto Internet network management protocol, in the management of smart environments. Since smart devices are typically resource constrained, we propose and develop an SNMP-based hierarchical management architecture to manage an environment composed of Arduino and Raspberry Pi boards. MIB extensions are developed and instrumented to support the proposed management architecture. Results demonstrate the feasibility of the SNMP protocol in managing smart devices without adding significant overheads.